KARAKTERISASI STRUKTUR NANO KARBON DARI LIGNOSELLULOSA - Gustan Pari; Adi Santoso; Djeni Hendra; Buchari; Akhirudin Maddu; Mamat Rachmat; Muji Harsini; Teddi Heryanto; Saptadi Darmawan (BRIN Publishing, 2013)
The science advancement in this century is such that in the future it will enter the nano technology. More specifically in the forest products field, the nano technology that can be developed is among others nano carbon derived from lignocelulosic stuffs. In relevant, this research aims to provide information and technology on the charcoal processing from lignocellulosic stuffs into nano carbon. The lignocellulosic stuffs used in this research consisted of teak wood and bamboo, further carbonized into charcoal at 400-500°C using drum kiln. The resulting charcoal was examined of its physical and chemical properties, crystalinity degree and dielectric characteristics, and then purified by re-carbonizing it at 800°C for 60 minutes. Prior to the purification, the charcoal sustained the doping (intercalation) process with Zn, Ni and Cu metals each respectively. After the purification, the charcoal was ground to very tiny particels using HEM (high energy machine) device for 48 bours. In this way, the charcoal with high crystalinity was yielded, and further sintered using spark plasma at 1,300 C into the nano carbon. The qualities and structure of all the resulting carbon (carbonized charcoal, re-carbonized charcoal, intercalated charcoal and sintered nano carbon) were evaluated using nano scale device (Py-GCMS, SEM-EDX and XRD), and examined as well of their dielectric characteristics. In turns out that the best quality charcoal was obtained from teak wood charcoal carbonized at 800°C, intercalated with Ni atoms at the ratio 1:5. The resulting charcoal afforded high crystalinity (78.98%), low electric resistance (0.17 2), and high conductivity 175.52 2'm Qualities of the corresponding nano carbon (after sintering) were such that its crystalinity spectaculary reached 81.87%, resistance (R) 0.01 & with very bigh conductivity 1067.262'm'. The nano carbon that resulted seems favorably prospective for bio-censor, bio-battery, and bio-electrode. Accordingly futher related research deserves carrying out.